Psychometric analysis on sustainability awareness and integration in managing higher educational institutions in Nigeria - Ayodele, Lasisi Abass; Mohd Ali, Hairuddin; Usman, Shuaibu Hassan (iSTEAMS Research Nexus 2013, 2013)
Sustainability is a concept moving around in conferences and as an important headword in higher educational curriculum especially environmental study and economics. This concept is understood as “capable of being sustained” (Franklin and Blyton, 2011). This study investigates the sustainability awareness and integration in managing educational institutions among students of Nigerian Higher Education Institutions (NHEI). The research employs Factor Analysis technique to confirm the sustainability awareness and integration in higher education institutions. The findings indicated that sustainability awareness and integration occur and appears in educational curriculum mostly environmental study and economic. The study suggested that the concept should firmly internalize in management of NHEI for quality achievement in educational services.